2009
DOI: 10.1111/j.1528-1167.2009.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Even a single seizure negatively impacts pediatric health‐related quality of life

Abstract: Summary Purpose:  Both a single seizure and chronic recurrent seizures (epilepsy) occur commonly in childhood. Although several studies have documented the impact of pediatric epilepsy on psychosocial functioning, such as health‐related quality of life (HRQOL), no studies have examined the impact of a single seizure on HRQOL. The primary objectives of this study were: (1) to compare parent–proxy HRQOL in children with a single seizure and newly diagnosed untreated epilepsy to normative data and (2) to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 37 publications
9
49
0
Order By: Relevance
“…Even a single seizure in children has been associated with a negative psychological effects and a decreased health-related quality of life. 30 Medically refractory epilepsy, multiple anticonvulsants, and comorbid neurologic impairments can further worsen quality of life. 31 It is possible that the seizures and epilepsy were not related to the stroke itself but rather an underlying genetic disorder or other brain injury such as neonatal hypoxic ischemic encephalopathy.…”
mentioning
confidence: 99%
“…Even a single seizure in children has been associated with a negative psychological effects and a decreased health-related quality of life. 30 Medically refractory epilepsy, multiple anticonvulsants, and comorbid neurologic impairments can further worsen quality of life. 31 It is possible that the seizures and epilepsy were not related to the stroke itself but rather an underlying genetic disorder or other brain injury such as neonatal hypoxic ischemic encephalopathy.…”
mentioning
confidence: 99%
“…Children and adolescents with epilepsy had significantly lower levels of functioning and well-being in physical, psychological (including emotional, general mental health, and selfesteem), social, school, and family domain compared to healthy controls, siblings, and/or the normative data (Miller et al, 2003;Montanaro et al, 2004;Modi et al, 2009;Haneef et al, 2010;Baca et al, 2010). One study reported that children and adolescents had significantly lower physical and school functioning compared to other chronic illnesses as self-rated, and lower physical, emotional, and social functioning as parent-rated (Haneef et al, 2010).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] Although several studies have examined factors associated with poor HRQoL in CWE, in these studies investigators have typically focused on the role of epilepsy-related factors like seizure severity and frequency, syndromes, number of antiepileptic drugs (AEDs) and toxicity, and sociodemographic variables. [30][31][32][33][34][35][36][37][38][39][40][41][42] Although a limited number of studies have revealed a negative association of comorbidity with HRQoL in CWE, no studies have been performed to examine the independent effects of chronic comorbidities, including psychiatric and neurodevelopmental disorders, on HRQoL in CWE nearly a decade after childhoodonset epilepsy. 30,[35][36][37]40,[43][44][45][46] In a community-based study of children with newly diagnosed epilepsy followed prospectively, we examined the relative impacts of 5-year remission and "complicated" epilepsy (secondary to an underlying neurologic insult or epileptic encephalopathy) status, in addition to chronic comorbidity (eg, psychiatric diagnosis, neurodevelopmental disorders, migraine, chronic medical conditions) to determine if they were differentially associated with HRQoL at follow-up during adolescence.…”
mentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42] Although a limited number of studies have revealed a negative association of comorbidity with HRQoL in CWE, no studies have been performed to examine the independent effects of chronic comorbidities, including psychiatric and neurodevelopmental disorders, on HRQoL in CWE nearly a decade after childhoodonset epilepsy. 30,[35][36][37]40,[43][44][45][46] In a community-based study of children with newly diagnosed epilepsy followed prospectively, we examined the relative impacts of 5-year remission and "complicated" epilepsy (secondary to an underlying neurologic insult or epileptic encephalopathy) status, in addition to chronic comorbidity (eg, psychiatric diagnosis, neurodevelopmental disorders, migraine, chronic medical conditions) to determine if they were differentially associated with HRQoL at follow-up during adolescence. Given evidence of persistent poor long-term psychosocial outcomes among children with childhoodonset epilepsy, even in the setting of seizure remission, in conjunction with evidence that psychiatric comorbidity is more strongly associated with HRQoL than epilepsy-related factors among adults with epilepsy, we hypothesized that psychiatric or neurodevelopmental comorbidity would be more strongly associated with worse long-term HRQoL than 5-year remission status.…”
mentioning
confidence: 99%